Efektivitas Metode Bercerita dalam Meningkatkan Kemampuan Siswa Memahami Isi Bacaan pada Mata Pelajaran Bahasa Indonesia - Ahmad Sa'adi; Wiranti Wiranti (TA'DIBAN, 2021)
The effectiveness of the storytelling method is not only known from the increasing ability of students to understand the content of reading in Indonesian subjects, but can be seen from the ability of teachers to apply the storytelling method. The role of the teacher in applying the storytelling method in improving students' ability to understand the contents of Indonesian reading is very much needed, so the teacher must have competence, namely a set of knowledge, skills and behaviors that must be possessed, internalized and mastered by the teacher in carrying out professional duties. The type of research used here is descriptive qualitative with a sampling technique that is purposive sampling. Collecting data through observation, interviews and documentation. By using data analysis techniques, namely data collection, data reduction, data presentation and drawing conclusions. The results of the data collected showed that the effectiveness of the storytelling method in improving students' ability to understand the content of reading in Indonesian subjects in class IV A SDII Luqman Al-Hakim 02 Batam is that in applying the storytelling method the role of the teacher should be needed in managing learning that has various abilities in terms of understanding students, as well as moving and motivating students to be enthusiastic in learning.